PENGELOLAAN SAMPAH TERPADU DI KOTA SEMARANG - Kustyardhi, Rizky; Suwitri, Sri; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Trash problem becomes quite serious problems that faced by government of Semarang city. The volume of trash grows every year. The Law No. 18 Year 2008 about Trash Management is a reference for government of Semarang city to change the way of trash management from get-haul waste into friendly environmental trash management by using the principle of the 3Rs (reduce, recycle, dan reuse).The purpose of this study is not only to describe and to analyze the implementation of integrated trash management in Semarang city but also to identify the inhibiting factors that occur in integrated trash management of Semarang city.To answer the problem and the purpose of this research, the writer uses descriptive qualitative approach by using management theory that focuses on the function of implementation of the plan, staffing, and coordination.The research shows that the inhibitor in the integrated trash management in Semarang city due to inadequate government budget, the difficulties in marketing the products of processed junk, poor coordination, and low public awareness in trash management.To improve the integrated trash management in Semarang city, the advices that can be given by writer to the Department of Hygiene and Gardening of Semarang city are to cooperate with the agencies that concerned in the problems of trash, to improve the coordination systems, to enforce regulations strictly, and to raise awareness continually in order to be wise in trash management.